Meta-análisis de la definición del uso racional de energía en varios países - Nova Arévalo, Néstor (Ingeniería, 2012)
In this article a statistical comparison of the definition issued by various countries on the concept of Rational Use of Energy - RUE - is carried out, using textual analysis as a method of semantic decomposition of concepts. Pearson's correlation coefficients were calculated and the correlation circles were constructed through principal component analysis. As a result, large differences were found between the definitions of the Latin-American countries and the European Union; the definition issued by Colombia being only similar to that of Mexico. We conclude that one of the reasons why Kyoto Protocol has not been successfully applied is due to divergent definitions of the concept of RUE, which modifies the planning horizon of each country; joint actions such as those of the European Community illustrate the effectiveness of strategies when there is a linking from conception to execution.